2019
DOI: 10.1097/fbp.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Early life exposure to cortisol in zebrafish (Danio rerio): similarities and differences in behaviour and physiology between larvae of the AB and TL strains

Abstract: Maternal stress and early life stress affect development. Zebrafish (Danio rerio) are ideally suited to study this, as embryos develop externally into free-feeding larvae. The objective of this study was therefore to assess the effects of increased levels of cortisol, mimicking thereby maternal stress, on larval physiology and behaviour. We studied the effects in two common zebrafish strains, that is, AB and Tupfel long-fin (TL), to assess strain dependency of effects. Fertilized eggs were exposed to a cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…These studies showed that, as a result of the cortisol exposure during early embryonic stages, larval baseline levels of cortisol were increased (10,13,14,21). For example, in a recent study, we have demonstrated that cortisol exposure between 0 and 6 hpf increased baseline cortisol levels 5 days post fertilization (dpf) of larvae from the AB strain (10).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…These studies showed that, as a result of the cortisol exposure during early embryonic stages, larval baseline levels of cortisol were increased (10,13,14,21). For example, in a recent study, we have demonstrated that cortisol exposure between 0 and 6 hpf increased baseline cortisol levels 5 days post fertilization (dpf) of larvae from the AB strain (10).…”
Section: Introductionmentioning
confidence: 90%
“…Cortisol has been shown to signal through the GR already during the very early stages of embryonic development; in oocytes maternally deposited cortisol and GR mRNA are present (7)(8)(9). These cortisol levels may reflect the allostatic load that the mothers experience in their environment and it has therefore been hypothesized that these deposited cortisol levels are important for preparing the offspring for the expected allostatic load that larvae will encounter in the prevailing environment, thereby programming their cortisol secretion and the functioning of physiological systems to meet expected demands (4,10). While in previous studies we focussed on the effects of cortisol exposure [between 0 and 6 h post fertilization (hpf)] on vigilance-related behavior, baseline cortisol levels and metabolism in larvae (10,11) in the present study we focussed on the functioning of the immune system, in particular the innate immune system on which zebrafish larvae rely (12).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations